Traffic Light Maintenance Training at The Transportation Office of Kulon Progo Regency - Helmi Wibowo; Riza Pahlevi; Hanif Adhi Yudhitami; Dhi Astuti (Institut Teknologi Nasional, Bandung, 2022)
In traffic regulation, Maintenance of Traffic Light Signaling Devices (APILL) is a competency that must be possessed by every employee of the Department of Transportation, so that every APILL at road intersections is able to regulate the speed of vehicles in an orderly manner. The method used was to provide education and training to employees of the Kulonprogo Department of Transportation for 5 (five) days. To measure the level of understanding of the training participants, pre-test and post-test were conducted. The average value of pre-test and post-test was 68 and 83 with an average increase of 16%. The conclusion of the APILL Maintenance Training at the Transportation Office of Kulon Progo Regency is said to be successful as indicated by the increase of the post test scores of all training participants. This shows the training participants understand the material well.